Adiponectin Participates in Preeclampsia by Regulating the Biological Function of Placental Trophoblasts through P38 MAPK-STAT5 Pathway - Gaoxia DONG; Ying TIAN; Xinqin LI (Tehran University of Medical Sciences, 2018)
Background: We aimed to investigate the participation of adiponectin in preeclampsia, and to explore the possible mechanism. Methods: A total of 52 patients with preeclampsia and 30 normal women with full-term pregnancy were enrolled. Immunohistochemistry was used to detect the localization of MAPK and STAT5. RT-PCR was used to detect the expression of adiponectin mRNA in placental tissue of patients with preeclampsia and normal pregnant women. Western blot was used to detect the expression of adiponectin protein, MAPK, p-MAPK, STAT5 and p-STAT5 in placental tissue of patients with preeclampsia and normal pregnant women. Results: p-p38 was highly expressed in placental trophoblasts of patients with preeclampsia, while p-STAT5 was less expressed. Expression level of p-p38 and p-STAT5 in patients with preeclampsia were significantly different from those in normal pregnant women (P<0.01). Expression level of adiponectin mRNA was significantly lower in patients with preeclampsia than in normal pregnant women (P<0.05). Level of p-p38 expression was negatively correlated with levels of adiponectin expression (r=-0.413, P<0.05). Expression level of p-STAT5 was positively correlated with expression level of adiponectin (r=0.526, P<0.01). Conclusion: Adiponectin participates in preeclampsia by regulating the biological function of placental trophoblasts through p38 MAPK-STAT5 pathway.